Effect of Blended Learning in high school Japanese Language Learning outcomes - Linda Maryati; Zainal Rafli; Samsi Setiadi (JTP - Jurnal Teknologi Pendidikan, 2022)
This study aimed to determine the effect of blended learning-based contextual learning and independent learning on Japanese language learning outcomes of students at SMA Negeri 1 Setu. The ability to read and write kana (hiragana and katakana) is very important for basic level Japanese learners to support learning at the next level. Blended learning-based learning is the best choice to increase effectiveness, efficiency, during the current pandemic. With blended learning, interaction and communication between students and between teachers and students can continue. This paper will discuss the meaning of blended learning, the advantages and disadvantages of blended learning and the design of blended learning implementation. This study aims to determine the ability of students in mastering hiragana letters and simple grammar using a blended learning model. The author uses online learning (e-learning) with Zoom and Google Classroom applications. This study used an experimental method with level 2 x 2 treatment. The sample of this study amounted to 35 students of class X Language SMAN 1 Setu Bekasi. The research instruments used were tests, questionnaires and observation sheets. The results of this study conclude that Gakkouno seikatsu learning outcomes are higher with contextual learning strategies with blended learning than conventional learning strategy. It is recommended that the blended learning strategy can be used as an alternative learning process in Japanese language learning.